A Reassessment of Well-Being in Vocational Preparation: A New Model Focusing on Psychological Resilience and Occupational Identification in Tourism Education - Mehmet Düzgün (Journal of Tourism, Sustainability and Well-being)
The fact that there is no alternative to technology and information communication technologies in the age we live in requires a close examination of the concept of technostress and the development of preventive approaches. If prospective employees aiming for a career in the tourism sector do not have sufficient resilience, they may not be ready for a long career plan due to the possible obstacles they may encounter in the sector. The study revealed the importance of relational resources in achieving and sustaining psychological resilience and professional identification. In addition, the study aimed to determine the effect of psychological resilience on technostress and the mediating role of professional identification in this effect. This study, which was designed in accordance with the causal screening model, was conducted with 393 students studying tourism. The findings of the study showed that psychological resilience positively affected occupational identification by reducing technostress. In addition, the findings emphasized that despite the technostress caused by the intensive use of technology, businesses with high psychological resilience and employees who are identified with their profession will provide competitive advantage in the tourism sector. Policy makers regarding human resources in tourism and educational institutions should focus on analyzing factors related to resilience and stress of employees or candidates/students.